FRI0125 Comparison of characteristics of international and national databases in rheumatoid arthritis: a systematic literature review. (23rd January 2014) - Gvozdenovic, E.; Koevoets, R.; Langenhoff, J.; Allaart, R.; Landewé, R.
Abstract : Background: RA cohorts and registers are established for daily practice in clinical care. Despite existing guidelines and international consensus about preferred drug therapies, there are still differences between registries in disease activity and outcome, which might be due to varying definitions for disease, inclusion criteria and variety in usage of biological agents. To improve collaboration between European rheumatologists, EULAR has recently started a repository of databases, which can be used as a platform for researchers to start collaborative projects Objectives: To perform a systematic review on international, national registers and observational cohorts in Europe, to inform on participation in the EULAR repository of databases, and compare inclusion criteria, registry aim, registry type and the extent of data collection. Methods: An extensive search strategy was performed in Pubmed, Embase, Web of Science (WOS), Academic Search Premier, Wiley-Blackwell and LWW. Articles reporting on European prospective cohorts in RA with at least half a year of follow-up and >200 patients included were selected. We extracted data on national and international databases with details on aim, size, selection criteria, year of inception, frequency of data collection, physician/clinical evaluation, patient reported outcomes, laboratory information, funding and rheumatologic diseases captured. Results: In total, 418 articles were included, which described 4 international and 39 national databases. International databases were roughly similar and are mostly initiated to monitor and compare clinical patient care among countries. Also no restriction was present in frequency of data collection and selection criteria. The national databases differ in clinical features, such as aims (Most registers aimed at efficacy and safety of treatment or monitoring disease activity in clinical practice), distribution among countries (not evenly distributed) and inclusion criteria (e.g. early RA registers versus routine care registers). Half of the national registers were connected to the EULAR repository of databases. Conclusions: International registries have similar characteristics and the patients represent a large range of clinical activity (from inactive to active) and severity (from mild to severe). Regarding the national databases heterogeneity is far greater, relevant differences exist in inclusion criteria, aims, frequency of data collection and distribution among Europe. Also only half of the databases are connected to the EULAR repository of databases. These differences may indicate that among researchers there is little awareness in guidelines to set up registers or cohorts and in the existence of the collaboration network of the EULAR Disclosure of Interest: None Declared